FORMULATION AND EVALUATION OF FLOATING TABLET OF ATENOLOL FOR THE TREATMENT OF HYPERTENSION - Km Sidra Zaya; Mrs.Jyoti Nayak; Dr .Jai Narayan Mishra (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The current study set out to develop a gastro-retentive atenolol floating tablet. Angina pectoris and hypertension are both treated with this beta-blocker (beta-adrenoreceptor antagonist). When used orally, it is only partially absorbed from the digestive system and only 50% of the medication is accessible; the other 25% is excreted unchanged in faeces. This problem results from insufficient absorption in the lower gastrointestinal system. To improve the oral bioavailability and therapeutic effectiveness of atenolol, the gastro-retentive floating drug delivery system (GFDDS) growth was deemed useful. The direct compression technique was used to make floating pills of atenolol (F1-F5). To reduce the floating delay, a polymer like HPMC was used together with gas-producing chemicals such citric acid and sodium bicarbonate. Evaluations were done on the blends, compressibility index, bulk density, Hausner's ratio, angle of repose and tapped density. Additionally evaluated were the tablets' hardness, diameter, weight variation, homogeneity of the drug content, friability, floating and buoyancy lag times, impact of hardness, in vitro swelling behavior, and in vitro release of drug. The USP dissolving test apparatus-II was utilised to rotate 900 cc of a hydrochloric acid buffer with a pH of 1.2 at 50 rpm while maintaining a 37.5°C temperature for the in-vitro release of drug examination